MULTI-COMMODITY INVENTORY MODEL FOR FREE NUTRITIOUS FOOD PROGRAMS BASED ON ECONOMIC ORDER QUANTITY, JUST-IN-TIME, AND REORDER POINT: A CASE STUDY OF GUNUNG SINDUR DISTRICT - Shanti Pujilestari; Siti Aminatu Zuhria; Handono Bayuadji (RADJA PUBLIKA, 2026)
The Free Nutritious Meal Program (MBG) requires efficient inventory management due to its routine distribution schedule and the involvement of food commodities with different shelf lives. This study evaluates MBG inventory management at the Nutrition Fulfillment Service Unit (SPPG) level in Gunung Sindur District using a multi-commodity framework based on Economic Order Quantity (EOQ), Just-in-Time (JIT), Reorder Point (ROP), and Safety Stock (SS), including an assessment of cold storage for vegetable commodities. A deterministic quantitative approach is applied, assuming a daily demand of 42,467 meal portions over 240 operational days per year. Rice and eggs are managed using EOQ with ROP and SS, while vegetables are analyzed under JIT and EOQ with cold storage. The results show annual distribution costs of IDR 399 million for rice and IDR 153 million for eggs. JIT-based vegetable distribution incurs the highest cost at IDR 720 million per year. Although cold storage reduces vegetable distribution costs to IDR 480 million per year, additional cold storage costs of IDR 529.2 million increase total system costs from IDR 1.272 billion (without cold storage) to IDR 1.561 billion (with cold storage). As of January 2026, only six of eight SPPG units are operational, serving 21,575 beneficiaries, indicating that at least 12 SPPG units are required to meet full MBG demand.